2004
DOI: 10.1039/b408041f
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-based synthesis of stacked calcium carbonate (calcite) superstructures

Abstract: Synthesis of calcium carbonate in water-in-oil microemulsions results in the spontaneous formation of stacked superstructures of 20 nm-thick pseudo-hexagonal calcite plates in crystallographic register.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 14 publications
1
35
2
1
Order By: Relevance
“…4a) indicate that the characteristic absorption bands at 712, 872 and 1420 cm À1 can be assigned to the in-plane bending (m4), out-of-plane bending (m2) and asymmetric stretching (m3) modes of CO 2À 3 of calcite, respectively. Significantly, weak bands were also observed at 2982, 2874, 2926 and 2853 cm À1 that was associated with asymmetric and symmetric methyl and methylene CAH stretches, respectively, and the peak at 1082 cm À1 was assigned to PAOAC stretch, suggesting that DNA molecules remained strongly combined with the calcite crystals even after extensive washing [46]. This was consistent with EDX analysis of the superstructures (as shown in Fig.…”
Section: Resultssupporting
confidence: 87%
“…4a) indicate that the characteristic absorption bands at 712, 872 and 1420 cm À1 can be assigned to the in-plane bending (m4), out-of-plane bending (m2) and asymmetric stretching (m3) modes of CO 2À 3 of calcite, respectively. Significantly, weak bands were also observed at 2982, 2874, 2926 and 2853 cm À1 that was associated with asymmetric and symmetric methyl and methylene CAH stretches, respectively, and the peak at 1082 cm À1 was assigned to PAOAC stretch, suggesting that DNA molecules remained strongly combined with the calcite crystals even after extensive washing [46]. This was consistent with EDX analysis of the superstructures (as shown in Fig.…”
Section: Resultssupporting
confidence: 87%
“…Additionally, by changing the width of the surfactant nanoparticle layer, the stability of the microcrystals can be controlled [22]. Besides varying stirring rate [23], other additives [24,25] or reaction media [26] can also be used, where the formation of vaterite from amorphous calcium carbonate is suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Such complexes, if synthesized, could have numerous important applications in many industries [9][10][11]. Studies have demonstrated that a promising approach is to use organic additives and/or templates to control nucleation, growth, and alignment in the synthesis of inorganic materials [12][13][14][15]. This strategy has led to the formation of a variety of shapes of CaCO 3 in recent years [16][17][18][19][20].…”
mentioning
confidence: 98%